Polyester resin with high impact resistance and super weather resistance and preparation process thereof
By adding components such as amino resin, acrylic polyol resin and modified filler to the polyester resin, a tight network structure is formed, which solves the problem of insufficient aging resistance of polyester resin and improves the impact and weatherability of the coating. , achieving better leveling effect and color stability.
Patent Information
- Application Number
- CN202411806215.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Among the existing ultra-weather resistant powder coatings, the aging resistance of polyester resin is insufficient, and the compatibility of polyamides and polyester resins is poor, which affects the physical properties and color stability of the coating.
Using a high impact ultra-weather-resistant polyester resin formula, including polyols, amino resins, acrylic polyol resins, modified fillers and specific acid dehydrants, a tight network is formed through cross-linking reactions and synergistic effects. Structure, improve the impact resistance and weather resistance of the resin.
It significantly improves the impact and weather resistance of the coating, improves the leveling effect and aging resistance of the coating, avoids yellowing, and enhances the thermal and chemical stability of the material.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyester resins, and in particular relates to a polyester resin with high impact and super weather resistance and a preparation process thereof. Background Art
[0002] In the thermosetting polyester powder coating industry, the most widely used in China is the polyester powder coating cured by triglycidyl isocyanurate (TGIC), followed by polyester powder coating cured by hydroxyalkylamide (HAA). Super weather-resistant powder coatings have longer-lasting weather resistance than conventional powder coatings, and the coating can meet the requirements of outdoor protection for more than 10 years. The curing agent of super weather-resistant powder coatings is generally triglycidyl isocyanurate (TGIC) or hydroxyalkylamide (primid). Due to the eco-toxicity of TGIC, it has been included in the production capacity elimination catalog by the Ministry of Industry and Information Technology, and the primid curing agent can prepare non-toxic, non-biomutation environmentally friendly powder coatings. Therefore, the primid system has become the mainstream development direction of super weather-resistant powder coatings.
[0003] Conventional primid system super weather-resistant polyester powder coatings are limited by the narrow range of monomer selection, high cost of special monomers, and the ester bond structure in the molecular structure that is easily hydrolyzed and has poor aging performance. It is extremely difficult to further improve the aging resistance of powder coatings. Since polyamide resin has excellent aging resistance, the powder coating industry often improves the weather resistance of the coating by physically blending polyamide resin with polyester resin.
[0004] Although it is a common practice in the powder coating industry to physically blend polyamide resins with polyester resins to improve the weather resistance of the coating. However, this method also faces some technical challenges: 1. Compatibility issues: The compatibility between polyamide resins and polyester resins is not very good, which leads to poor physical properties of the mixed materials, such as stratification or uneven dispersion. 2. Changes in rheological properties: The addition of polyamide will change the rheological properties of the mixed system, affecting the fluidity of the coating film and the quality of the final coating. For example, it will cause the coating surface to be uneven or orange peel-like. 3. Effect of curing reaction: The addition of polyamide will affect the curing process of polyester resin, including curing speed, degree of curing, etc., which will affect the mechanical strength and other physical and chemical properties of the final product. 4. Color stability: The addition of polyamide resin will affect the color stability of the coating, especially when exposed to ultraviolet rays for a long time, causing the coating to fade or yellow.
[0005] Therefore, there is an urgent need for a polyester resin with high impact and super weather resistance and a preparation process thereof. Summary of the invention
[0006] The purpose of the present invention is to address the shortcomings of the existing HAA curing system polyester resin powder coating, and to provide a polyester resin with high impact and super weather resistance and a preparation process thereof. The powder coating made of the resin has an intact coating surface after being boiled in boiling water for 48 hours, subjected to an impact resistance test and salt spray aging, and its impact resistance and weather resistance are significantly improved.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A polyester resin with high impact and super weather resistance comprises the following components in parts by weight: 30-40 parts of polyol, 40-55 parts of dibasic acid and / or anhydride, 15-25 parts of amino resin, 8-12 parts of acrylic polyol resin, 5-20 parts of acidolysis agent, 1-5 parts of polyamide, 0.1-0.5 parts of esterification catalyst, 10-20 parts of modified filler, 2-4 parts of curing accelerator and 0.1-1.5 parts of antioxidant.
[0009] Furthermore, the preparation method of the amino resin comprises the following steps: by weight, 34-39 parts of paraformaldehyde and 16-20 parts of ethylene glycol are uniformly mixed, the temperature is raised to 70-75° C., the temperature is kept for reaction for 1-2 hours, 20-24 parts of melamine are continuously added, the temperature is raised to 90-95° C., the temperature is kept for reaction for 40-60 minutes, the temperature is lowered to 50-55° C., 5-10 parts of N-aminoethylpiperazine, 12-16 parts of diethylenetriamine and 8-13 parts of 3-amino-n-butanol and 0.6-0.8 parts of ammonium chloride are added, and the reaction is carried out at 50-55° C. for 60-80 minutes to obtain the amino resin.
[0010] The invention can improve the impact resistance of the product by adding amino resin to polyester resin. The amino groups in the amino resin can undergo cross-linking reaction with carboxyl groups or other active groups in the polyester resin to form a more compact network structure. Multiple amino groups in N-aminoethylpiperazine, diethylenetriamine and 3-amino-n-butanol can undergo condensation reaction with hydroxymethylated melamine to form a highly cross-linked network structure, and the longer chain segments can increase the flexibility of the resin.
[0011] Furthermore, the acrylic polyol resin comprises acrylic polyol resin I, acrylic polyol resin II and acrylic polyol resin III in a weight ratio of 1: (1.2-1.5): (0.6-0.8); the viscosity of acrylic polyol resin I is 4500±1000cps, and the hydroxyl value is 147mgKOH / g; the viscosity of acrylic polyol resin II is 7000-10000cps, and the hydroxyl value is 125mgKOH / g; the viscosity of acrylic polyol resin III is 6500±2001cps, and the hydroxyl value is 87mgKOH / g.
[0012] The present invention can improve the wear resistance of polyester resin by adding three different acrylic polyol resins in a specific proportion. This is mainly because by adding three different acrylic polyol resins in a specific proportion, a synergistic effect of multiple components can be achieved, and this synergistic effect can significantly improve the comprehensive performance of polyester resin, especially wear resistance; each acrylic polyol resin has different chemical structures and performance characteristics, and they can complement each other's deficiencies after mixing to form a better performance combination and improve the wear resistance of polyester products.
[0013] Furthermore, the preparation method of the modified filler comprises the following steps:
[0014] (1) mixing silicon dioxide, lanthanum oxide and multi-walled carbon nanotubes to obtain a mixed filler;
[0015] (2) Mixing a mixed filler, KH550, ethanol and water in a weight ratio of 1: (0.5-0.7): (15-18): (4-8), reflux at 70-75° C. for 4-6 hours, filtering and drying to obtain a pre-modified filler;
[0016] (3) mixing p-aminostyrene, 3-mercaptopropyltrimethoxysilane and tetrahydrofuran in a weight ratio of (0.65-0.75):1:(6-8), reacting at 25-30°C and a light intensity of 2000-4000 lux for 26-28 hours to obtain an intermediate;
[0017] (4) Mix 2-2.5 mL of aniline and 12-15% hydrochloric acid at a pH of 2.0-2.3, add 4 mg of pre-modified filler, 0.4-0.6 g of intermediate and ammonium persulfate, react at 4-6 °C for 17-20 h, filter and dry to obtain a modified filler.
[0018] 3-Mercaptopropyltrimethoxysilane, CAS: 4420-74-0.
[0019] Furthermore, the weight ratio of silicon dioxide, lanthanum oxide and multi-walled carbon nanotubes is (1.5-1.7):1:(0.2-0.4).
[0020] Furthermore, the average particle size of silicon dioxide is 15 nm and the specific surface area is 250 m 2 / g; purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-SiO2-15; lanthanum oxide crystal nucleus particle size is 40nm, specific surface area is 125m 2 / g, purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-La2O3-40; multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of 50 nm were purchased from Xianfeng Nano.
[0021] The present invention can improve the boiling resistance of polyester resin by using three different fillers with specific parameters for modification. Because the modified filler is more evenly dispersed in the system and has better compatibility with other components in the system, the hydroxyl groups on the surface of silica can undergo cross-linking reactions with active groups (such as carboxyl and hydroxyl) in the polyester resin system to form a more compact network structure. This cross-linking structure can improve the water resistance and heat resistance of the material; lanthanum oxide has high heat resistance and chemical resistance, which can improve the thermal stability and chemical stability of polyester resin, thereby enhancing the boiling resistance; the high aspect ratio and nanoscale characteristics of multi-walled carbon nanotubes enable it to form a dense physical barrier to prevent moisture from penetrating into the interior of the material, thereby improving the boiling resistance.
[0022] Furthermore, the dosage of ammonium persulfate is 4-6% of the mass of aniline.
[0023] Furthermore, the esterification catalyst is monobutyltin oxide.
[0024] Furthermore, the curing accelerator is allnex EBECRYL436.
[0025] Furthermore, the acidolysis agent is diphenylaminodiphenylamine or adipic acid.
[0026] Furthermore, the antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant in a weight ratio of 1:1.
[0027] The present invention also provides a preparation process of the polyester resin with high impact and super weather resistance, comprising the following steps:
[0028] (1) In a nitrogen atmosphere, polyol, dibasic acid and / or anhydride, polyamide and esterification catalyst are added to a reaction kettle in sequence, and the temperature is gradually raised to 150-160°C while stirring, and then the temperature is further raised to 250-260°C at a heating rate of 8-10°C / h, and the temperature is kept for 4-5h to react until the acid value reaches 4-12mgKOH / g;
[0029] (2) Under nitrogen atmosphere, cool the reactor to 230-240°C, add polyamide, continue to keep the temperature for reaction for 1-2 hours, add acidolysis agent, keep the temperature for 4-5 hours, test the acid value range is 2-6 mgKOH / g, cool to 200-210°C and start vacuuming, and keep the pressure of the reactor at -0.095 MPa;
[0030] (3) Continue to add the remaining components, stir for 20-40 minutes, discharge, cool and crush to obtain a light yellow transparent granular material, which is a polyester resin with high impact and super weather resistance.
[0031] The design idea of the present invention is to synthesize modified polyester by adding polyamide monomers and use diphenylamine diphenylamine as an acidolysis agent. The prepared modified polyester overcomes the defects of polyester resin in weather resistance. The powder coating prepared by the resin shows better comprehensive performance in terms of impact resistance, leveling effect, aging resistance and storage stability. The powder coating also includes additives such as curing agent, leveling agent, brightener, filler and pigment. The curing agent is HAA.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention prepares a polyester resin suitable for a Primid system super-weather-resistant powder coating by adding polyamide monomers into a resin formula, studying the effects of the order and amount of polyamide addition on the properties of the modified polyester, and investigating the effect of an acidolysis agent on the properties of the polyester.
[0034] (2) The present invention synthesizes polyester resin by introducing polyamide monomers. After introducing the chain macromolecular polymer of the amide group (CNOH structure) into the polyester molecule, it has the unique characteristics of low specific gravity, high tensile strength, wear resistance, good self-lubrication, excellent impact toughness and both rigidity and flexibility.
[0035] (3) The present invention also optimizes the amount of trimethylolpropane used. Its branched structure increases the cross-linking density of the resin during curing, reduces the mobility of the molecules, makes the lipid bonds more difficult to hydrolyze, and enhances its salt spray resistance.
[0036] (4) The present invention improves the weather resistance of polyester resin by controlling the acid value, which not only avoids the situation that the acid value is too low so that the epoxy groups of HAA do not participate in the reaction and reduce the crosslinking density of the polyester resin, but also prevents the acid value from being too high so that the hydrophilic -COOH residues catalyze the hydrolysis of lipid bonds.
[0037] (5) The present invention optimizes the use of antioxidants and no longer adds phosphite antioxidants, thereby improving the impact resistance and weather resistance of polyester resins.
[0038] (6) The present invention can improve the impact resistance of the product by adding amino resin to polyester resin.
[0039] (7) The present invention can improve the wear resistance of polyester resin by adding three different acrylic polyol resins in a specific ratio.
[0040] (8) The present invention can improve the boiling resistance of polyester resin by using three different fillers with specific parameters for modification. DETAILED DESCRIPTION
[0041] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0042] Example 1
[0043] The present embodiment provides a polyester resin with high impact and super weather resistance, comprising the following components in parts by weight: 35 parts of neopentyl glycol, 50 parts of isophthalic acid, 20 parts of amino resin, 10 parts of acrylic polyol resin, 10 parts of acidolysis agent (adipic acid), 4 parts of polyamide (BASF, nylon 66 resin), 0.3 parts of esterification catalyst, 15 parts of modified filler, 3 parts of curing accelerator and 1.0 parts of antioxidant.
[0044] The esterification catalyst is monobutyl tin oxide. The curing accelerator is allnex EBECRYL 436. The antioxidant is a mixture of a hindered phenol antioxidant (Guangzhou Zhiyi Chemical Co., Ltd., model, YINOX®235) and a phosphite antioxidant (Guangzhou Zhiyi Chemical Co., Ltd., model, YIPHOS®3010W) in a weight ratio of 1:1.
[0045] The preparation method of the amino resin comprises the following steps: mixing 36 parts of paraformaldehyde and 18 parts of ethylene glycol uniformly by weight, heating to 72°C, keeping the temperature for reaction for 1.5 hours, adding 22 parts of melamine, heating to 92°C, keeping the temperature for reaction for 50 minutes, cooling to 52°C, adding 8 parts of N-aminoethylpiperazine, 15 parts of diethylenetriamine, 10 parts of 3-amino-n-butanol and 0.7 parts of ammonium chloride, reacting at 52°C for 70 minutes, and obtaining the amino resin.
[0046] Paraformaldehyde, Brand: Sigma-Aldrich. Product No. 441244.
[0047] N-Aminoethylpiperazine, CAS: 140-31-8.
[0048] The acrylic polyol resin includes acrylic polyol resin I, acrylic polyol resin II and acrylic polyol resin III in a weight ratio of 1:1.4:0.7; the viscosity of acrylic polyol resin I is 4500±1000cps, the hydroxyl value is 147mgKOH / g, purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU4470; the viscosity of acrylic polyol resin II is 7000-10000cps, the hydroxyl value is 125mgKOH / g, purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU3780; the viscosity of acrylic polyol resin III is 6500±2001cps, the hydroxyl value is 87mgKOH / g, purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU2655.
[0049] The preparation method of the modified filler comprises the following steps:
[0050] (1) mixing silicon dioxide, lanthanum oxide and multi-walled carbon nanotubes in a weight ratio of 1.6:1:0.3 to obtain a mixed filler;
[0051] (2) Mixing a mixed filler, KH550, ethanol and water in a weight ratio of 1:0.6:16:6, reflux at 72°C for 5 hours, filtering and drying to obtain a pre-modified filler;
[0052] (3) p-Aminostyrene, 3-mercaptopropyltrimethoxysilane and tetrahydrofuran in a weight ratio of 0.7:1:7 were mixed and reacted at 27°C and a light intensity of 3000 lux for 27 hours to obtain an intermediate;
[0053] (4) Mix 2.5 mL of aniline and 14% hydrochloric acid at a pH of 2.2, then add 4 mg of pre-modified filler, 0.5 g of intermediate and ammonium persulfate (the amount of ammonium persulfate is 5% of the mass of aniline); react at 5 °C for 18 h, filter and dry to obtain a modified filler.
[0054] 3-Mercaptopropyltrimethoxysilane, CAS: 4420-74-0.
[0055] The average particle size of silicon dioxide is 15nm and the specific surface area is 250m 2 / g; purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-SiO2-15; lanthanum oxide crystal nucleus particle size is 40nm, specific surface area is 125m 2 / g, purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-La2O3-40; multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of 50 nm were purchased from Xianfeng Nano.
[0056] The preparation process of the polyester resin with high impact and super weather resistance comprises the following steps:
[0057] (1) Under a nitrogen atmosphere, neopentyl glycol, isophthalic acid, polyamide and esterification catalyst were added to a reactor in sequence, and the temperature was gradually raised to 155°C while stirring, and then the temperature was further raised to 255°C at a heating rate of 9°C / h, and kept at this temperature for 4.5h;
[0058] (2) Under nitrogen atmosphere, the reactor was cooled to 235°C, polyamide was added, and the reaction was continued for 1.5 hours. Then, an acidolysis agent was added, and the reaction was continued for 4.5 hours. The reactor was cooled to 205°C and vacuum was started. The pressure of the reactor was maintained at -0.095 MPa.
[0059] (3) Continue to add the remaining components and stir for 30 minutes. Discharge, cool and crush to obtain a light yellow transparent granular material, which is a polyester resin with high impact and super weather resistance.
[0060] Example 2
[0061] The present embodiment provides a polyester resin with high impact and super weather resistance, comprising the following components in parts by weight: 34 parts of neopentyl glycol, 55 parts of isophthalic acid, 25 parts of amino resin, 8 parts of acrylic polyol resin, 14 parts of acidolysis agent (adipic acid), 5 parts of polyamide (BASF, nylon 66 resin), 0.5 parts of esterification catalyst, 10 parts of modified filler, 4 parts of curing accelerator and 1.5 parts of antioxidant.
[0062] The esterification catalyst is monobutyl tin oxide. The curing accelerator is allnex EBECRYL 436. The antioxidant is a mixture of a hindered phenol antioxidant (Guangzhou Zhiyi Chemical Co., Ltd., model, YINOX®235) and a phosphite antioxidant (Guangzhou Zhiyi Chemical Co., Ltd., model, YIPHOS®3010W) in a weight ratio of 1:1.
[0063] The preparation method of the amino resin comprises the following steps: mixing 34 parts of paraformaldehyde and 20 parts of ethylene glycol uniformly by weight, heating to 70°C, keeping the temperature for reaction for 2 hours, adding 20 parts of melamine, heating to 95°C, keeping the temperature for reaction for 40 minutes, cooling to 55°C, adding 5 parts of N-aminoethylpiperazine, 16 parts of diethylenetriamine, 8 parts of 3-amino-n-butanol and 0.8 parts of ammonium chloride, reacting at 50°C for 80 minutes, and obtaining the amino resin.
[0064] Paraformaldehyde, Brand: Sigma-Aldrich. Product No. 441244.
[0065] N-Aminoethylpiperazine, CAS: 140-31-8.
[0066] The acrylic polyol resin includes acrylic polyol resin I, acrylic polyol resin II and acrylic polyol resin III in a weight ratio of 1:1.2:0.6; the viscosity of acrylic polyol resin I is 4500±1000cps, the hydroxyl value is 147mgKOH / g, purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU4470; the viscosity of acrylic polyol resin II is 7000-10000cps, the hydroxyl value is 125mgKOH / g, purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU3780; the viscosity of acrylic polyol resin III is 6500±2001cps, the hydroxyl value is 87mgKOH / g, purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU2655.
[0067] The preparation method of the modified filler comprises the following steps:
[0068] (1) mixing silicon dioxide, lanthanum oxide and multi-walled carbon nanotubes in a weight ratio of 1.5:1:0.4 to obtain a mixed filler;
[0069] (2) Mixing a mixed filler, KH550, ethanol and water in a weight ratio of 1:0.5:15:8, reflux at 70°C for 6 hours, filtering and drying to obtain a pre-modified filler;
[0070] (3) p-Aminostyrene, 3-mercaptopropyltrimethoxysilane and tetrahydrofuran in a weight ratio of 0.65:1:8 were mixed and reacted at 30°C and a light intensity of 2000 lux for 28 hours to obtain an intermediate;
[0071] (4) Mix 2 mL of aniline and 15% hydrochloric acid at a pH of 2.3, and continue to add 4 mg of pre-modified filler, 0.6 g of intermediate and ammonium persulfate, with the amount of ammonium persulfate being 4% of the mass of aniline; react at 6 °C for 17 h, filter, and dry to obtain a modified filler.
[0072] 3-Mercaptopropyltrimethoxysilane, CAS: 4420-74-0.
[0073] The average particle size of silicon dioxide is 15nm and the specific surface area is 250m 2 / g; purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-SiO2-15; lanthanum oxide crystal nucleus particle size is 40nm, specific surface area is 125m 2 / g, purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-La2O3-40; multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of 50 nm were purchased from Xianfeng Nano.
[0074] The preparation process of the polyester resin with high impact and super weather resistance comprises the following steps:
[0075] (1) Under a nitrogen atmosphere, neopentyl glycol, isophthalic acid, polyamide and esterification catalyst were added to a reaction kettle in sequence, and the temperature was gradually raised to 160°C while stirring, and then the temperature was further raised to 250-260°C at a heating rate of 8°C / h, and kept at this temperature for 4-5h;
[0076] (2) Under nitrogen atmosphere, the reactor was cooled to 240°C, polyamide was added, and the reaction was continued for 1 hour. Then, an acidolysis agent was added, and the reaction was continued for 5 hours. The reactor was cooled to 210°C and vacuum was started. The pressure of the reactor was maintained at -0.095 MPa.
[0077] (3) Continue to add the remaining components and stir for 40 minutes. Discharge, cool and crush to obtain a light yellow transparent granular material, which is a polyester resin with high impact and super weather resistance.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that the amino resin and acrylic polyol resin components are different.
[0080] A polyester resin with high impact and super weather resistance comprises the following components in parts by weight: 35 parts of neopentyl glycol, 50 parts of isophthalic acid, 10 parts of amino resin, 20 parts of acrylic polyol resin, 10 parts of acidolysis agent (adipic acid), 4 parts of polyamide, 0.3 parts of esterification catalyst, 15 parts of modified filler, 3 parts of curing accelerator and 1.0 parts of antioxidant.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that the proportions of N-aminoethylpiperazine, diethylenetriamine and 3-amino-n-butanol are different.
[0083] The preparation method of the amino resin comprises the following steps: mixing 36 parts of paraformaldehyde and 18 parts of ethylene glycol uniformly by weight, heating to 72°C, keeping the temperature for reaction for 1.5 hours, adding 22 parts of melamine, heating to 92°C, keeping the temperature for reaction for 50 minutes, cooling to 52°C, adding 18 parts of N-aminoethylpiperazine, 10 parts of diethylenetriamine, 5 parts of 3-amino-n-butanol and 0.7 parts of ammonium chloride, reacting at 52°C for 70 minutes, and obtaining the amino resin.
[0084] Comparative Example 3
[0085] The difference between this comparative example and Example 1 is that the acrylic polyol resin includes acrylic polyol resin I, acrylic polyol resin II and acrylic polyol resin III in a weight ratio of 1:1:1; the viscosity of acrylic polyol resin I is 4500±1000cps, the hydroxyl value is 147mgKOH / g, and it is purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU4470; the viscosity of acrylic polyol resin II is 7000-10000cps, the hydroxyl value is 125mgKOH / g, and it is purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU3780; the viscosity of acrylic polyol resin III is 6500±2001cps, the hydroxyl value is 87mgKOH / g, and it is purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU2655.
[0086] Comparative Example 4
[0087] The difference between this comparative example and Example 1 is that the acrylic polyol resin is acrylic polyol resin I; the viscosity of acrylic polyol resin I is 4500±1000cps, the hydroxyl value is 147mgKOH / g, and it is purchased from Shandong Kafule Polymer Materials Co., Ltd. Jinan Branch, model CFU4470.
[0088] Comparative Example 5
[0089] The difference between this comparative example and Example 1 is that silicon dioxide, lanthanum oxide and multi-walled carbon nanotubes are mixed in a weight ratio of 1:1:1 to obtain a mixed filler.
[0090] Comparative Example 6
[0091] The difference between this comparative example and Example 1 is that the average particle size of silicon dioxide is 60nm, the specific surface area is 150-200m 2 / g; purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-SiO2-60. The crystal nucleus size of lanthanum oxide is 500nm, and the specific surface area is 20m 2 / g, purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-La2O3-500; multi-walled carbon nanotubes with a length of 10-30 microns and a diameter of 10-20 nm. Purchased from Xianfeng Nano.
[0092] Performance Testing
[0093] 1. The high-impact and super-weather-resistant polyester resin prepared in Example 1-2 was used as a sample for performance testing.
[0094] (1) Acid value test
[0095] Take 1g of sample and dissolve it in DMF. After it is completely dissolved, add phenolphthalein and titrate it with KOH solution. The acid value is calculated by the following formula:
[0096]
[0097] Where V is the volume of the KOH solution used, c is the concentration of the KOH solution, 56.11 g / mol is the molar mass of KOH, and m is the sample mass. The specific test method refers to the national standard GB / T6743-2008.
[0098] (2) Viscosity test
[0099] Use a viscometer to measure the viscosity of the sample, set the temperature to 200°C, and after the temperature stabilizes, take an appropriate amount of polyester sample, place it in the center of the test bench, and measure the viscosity.
[0100] (3) DSC test
[0101] The sample was tested using a differential scanning calorimeter. 10 mg of the sample was weighed and placed on the stage. After setting the parameters in the program, DSC measurement was performed. The measurement temperature range was 25-90°C and the heating rate was 10°C / min.
[0102] The results are shown in Table 1.
[0103] Table 1 Performance test results of polyester resin
[0104] 2. Use the high-impact and super-weather-resistant polyester resin prepared in Examples 1-2 and Comparative Examples 1-6 to prepare a coating. The formula includes, in terms of mass percentage: 55% of high-impact and super-weather-resistant polyester resin, 4.2% of HAA (tetrakis(β-hydroxyethyl) adipamide), 1.5% of leveling agent (BYK-371 from Germany), 0.9% of defoaming agent (Shengbang Silicone SI-X101), 0.9% of benzoin, 19.5% of titanium dioxide, and 18% of barium sulfate.
[0105] All raw materials were premixed, extruded, tableted and crushed through a twin-screw extruder, and then the flakes were crushed and passed through a 200-mesh sieve. They were then sprayed on an aluminum plate by electrostatic spraying, cured at 200°C for 10 minutes, and then the performance was tested.
[0106] Gloss is measured according to the provisions of GB / T9754-2007, with an incident angle of 60°; hydrolysis resistance is tested for 48 hours of boiling water resistance according to GB / T1733-1993, impact resistance is tested according to GB / T1732-2020; salt spray resistance is tested according to GB / T1771-2007. Wear resistance is tested according to GB / T23988-2009 "Sandfalling Method for Determination of Wear Resistance of Coatings", in which the larger the value of wear resistance, the more sandfalling is required for unit coating wear, indicating that the wear resistance of the coating is better.
[0107] The results are shown in Table 2.
[0108] Table 2 Coating performance test results
[0109] From the above performance test results, it can be seen that the coating prepared with the high-impact and super-weather-resistant polyester resin in Example 1-2 has excellent performance, which is mainly due to the synergistic effect between the components.
[0110] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the components of amino resin and acrylic polyol resin are different, and it can be seen that the comprehensive effect of the coating is reduced, proving that the two components play a synergistic effect in the system. In comparative example 2, the parts of N-aminoethylpiperazine, diethylenetriamine and 3-amino n-butanol used to prepare amino resin are different, and the results show that the impact resistance effect is reduced; the compositions of acrylic polyol resins in comparative examples 3 and 4 are different, and the wear resistance of polyester resin is reduced. The ratio of fillers in comparative example 5 is different, and the parameters of fillers in comparative example 6 are different, and the water boiling resistance of polyester resin is reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0111] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A polyester resin with high impact and super weather resistance, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of polyol, 40-55 parts of dibasic acid and / or anhydride, 15-25 parts of amino resin, 8-12 parts of acrylic polyol resin, 5-20 parts of acidolysis agent, 1-5 parts of polyamide, 0.1-0.5 parts of esterification catalyst, 10-20 parts of modified filler, 2-4 parts of curing accelerator and 0.1-1.5 parts of antioxidant; The preparation method of the modified filler comprises the following steps: (1) mixing silicon dioxide, lanthanum oxide and multi-walled carbon nanotubes to obtain a mixed filler; (2) Mixing a mixed filler, KH550, ethanol and water in a weight ratio of 1: (0.5-0.7): (15-18): (4-8), reflux at 70-75° C. for 4-6 hours, filtering and drying to obtain a pre-modified filler; (3) mixing p-aminostyrene, 3-mercaptopropyltrimethoxysilane and tetrahydrofuran in a weight ratio of (0.65-0.75):1:(6-8), reacting at 25-30°C and a light intensity of 2000-4000 lux for 26-28 hours to obtain an intermediate; (4) Mix 2-2.5 mL of aniline and 12-15% hydrochloric acid at a pH of 2.0-2.3, add 4 mg of pre-modified filler, 0.4-0.6 g of intermediate and ammonium persulfate, react at 4-6 °C for 17-20 h, filter and dry to obtain a modified filler; The weight ratio of silicon dioxide, lanthanum oxide and multi-walled carbon nanotubes is (1.5-1.7):1:(0.2-0.4).
2. The high-impact and super-weather-resistant polyester resin according to claim 1, characterized in that: The preparation method of the amino resin comprises the following steps: mixing 34-39 parts of polyformaldehyde and 16-20 parts of ethylene glycol uniformly by weight, heating to 70-75°C, keeping the temperature for reaction for 1-2 hours, adding 20-24 parts of melamine, heating to 90-95°C, keeping the temperature for reaction for 40-60 minutes, cooling to 50-55°C, adding 5-10 parts of N-aminoethylpiperazine, 12-16 parts of diethylenetriamine and 8-13 parts of 3-amino-n-butanol and 0.6-0.8 parts of ammonium chloride, reacting at 50-55°C for 60-80 minutes, and obtaining the amino resin.
3. The high-impact and super-weather-resistant polyester resin according to claim 1, characterized in that: The acrylic polyol resin comprises acrylic polyol resin I, acrylic polyol resin II and acrylic polyol resin III in a weight ratio of 1: (1.2-1.5): (0.6-0.8); the viscosity of acrylic polyol resin I is 4500±1000cps, and the hydroxyl value is 147mgKOH / g; the viscosity of acrylic polyol resin II is 7000-10000cps, and the hydroxyl value is 125mgKOH / g; the viscosity of acrylic polyol resin III is 6500±2001cps, and the hydroxyl value is 87mgKOH / g.
4. The high-impact and super-weather-resistant polyester resin according to claim 1, characterized in that: The average particle size of silicon dioxide is 15nm and the specific surface area is 250m 2 / g; the crystal nucleus size of lanthanum oxide is 40nm, and the specific surface area is 125m 2 / g; the length of the multi-walled carbon nanotubes is 0.5-2 microns and the diameter is 50nm.
5. The high-impact and super-weather-resistant polyester resin according to claim 1, characterized in that: The dosage of ammonium persulfate is 4-6% of the mass of aniline.
6. The high-impact and super-weather-resistant polyester resin according to claim 1, characterized in that: The esterification catalyst is monobutyltin oxide.
7. The high-impact and super-weather-resistant polyester resin according to claim 1, characterized in that: The acidolysis agent is diphenylaminodiphenylamine or adipic acid.
8. The high-impact and super-weather-resistant polyester resin according to claim 1, characterized in that: The antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant in a weight ratio of 1:
1.
9. A process for preparing a polyester resin with high impact and super weather resistance as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (1) In a nitrogen atmosphere, polyol, dibasic acid and / or anhydride, polyamide and esterification catalyst are added to a reaction kettle in sequence, and the temperature is gradually raised to 150-160°C while stirring, and then the temperature is further raised to 250-260°C at a heating rate of 8-10°C / h, and the temperature is kept for 4-5h to react until the acid value reaches 4-12mgKOH / g; (2) Under nitrogen atmosphere, cool the reactor to 230-240°C, add polyamide, continue to keep the temperature for reaction for 1-2 hours, add acidolysis agent, keep the temperature for 4-5 hours, test the acid value range is 2-6 mgKOH / g, cool to 200-210°C and start vacuuming, and keep the pressure of the reactor at -0.095 MPa; (3) Continue to add the remaining components, stir for 20-40 minutes, discharge, cool and crush to obtain a polyester resin with high impact and super weather resistance.
Citation Information
Patent Citations
Polyester resin for high-weather-resistance low-temperature HAA cured powder coating and preparation method of polyester resin
CN111621007A
Polyester resin with excellent yellowing resistance for powder coating and preparation method of polyester resin
CN114316227A
Light-color antistatic PET (Polyethylene Terephthalate) resin and preparation method and application thereof
CN116731297A
Cited By
Composite coating based on modified hydrogenated bisphenol A epoxy resin and preparation method thereof
CN119463648A
Anticorrosive acrylic resin coating and preparation method thereof
CN120464242A